Alkaliphilus flagellatus sp. nov., Butyricicoccus intestinisimiae sp. nov., Clostridium mobile sp. nov., Clostridium simiarum sp. nov., Dysosmobacter acutus sp. nov., Paenibacillus brevis sp. nov., Peptoniphilus ovalis sp. nov. and Tissierella simiarum sp. nov., isolated from monkey faeces. Issue 3 (8th March 2022) - Li, Dan-Hua; Abuduaini, Rexiding; Du, Meng-Xuan; Wang, Yu-Jing; Chen, Hong-He; Zhou, Nan; Zhu, Hai-Zhen; Lu, Yong; Yu, Pei-Jun; Yang, Yun-Peng; Jiang, Cheng-Ying; Sun, Qiang; et al.
Abstract : Non-human primates harbour diverse microbiomes in their guts. As a part of the China Microbiome Initiatives, we cultivated and characterized the gut microbiome of cynomolgus monkeys ( Macaca fascicularis ). In this report, we communicate the characterization and taxonomy of eight bacterial strains that were obtained from faecal samples of captive cynomolgus monkeys. The results revealed that they represented eight novel bacterial species. The proposed names of the eight novel species are Alkaliphilus flagellatus (type strain MSJ-5 T =CGMCC 1.45007 T =KCTC 15974 T ), Butyricicoccus intestinisimiae MSJd-7 T (MSJd-7 T =CGMCC 1.45013 T =KCTC 25112 T ), Clostridium mobile (MSJ-11 T =CGMCC 1.45009 T =KCTC 25065 T ), Clostridium simiarum (MSJ-4 T =CGMCC 1.45006 T =KCTC 15975 T ), Dysosmobacter acutus (MSJ-2 T =CGMCC 1.32896 T =KCTC 15976 T ), Paenibacillus brevis MSJ-6 T (MSJ-6 T =CGMCC 1.45008 T =KCTC 15973 T ), Peptoniphilus ovalis (MSJ-1 T =CGMCC 1.31770 T =KCTC 15977 T ) and Tissierella simiarum (MSJ-40 T =CGMCC 1.45012 T =KCTC 25071 T ).